Role of vitamins in the pathogenesis and treatment of restless leg syndrome: A systematic review and meta-analysis - Xiao-Min Xu; Jiang-hai Ruan; Tao Tao; Shu-li Xiang; Ren-liang Meng; Xiu Chen (PLoS ONE, 2025)
We performed a meta-analysis to assess the role of vitamins in the possible pathogenesis and treatment of RLS (Restless Leg Syndrome). A systematic search of the PubMed, Cochrane, Embase, and Web of Science databases was conducted. Fifty-nine studies on the relationship between vitamins and RLS were included, as well as four randomized controlled trials (RCTs) on vitamin treatment of RLS. Compared with non-RLS patients, serum vitamin D levels were significantly lower both in primary (P =  0.009) and secondary (P =  0.003) RLS patients, and appeared to be positively correlated with disease severity. Serum folate levels were lower in pregnant RLS patients than in pregnant non-RLS patients (P =  0.007), but this phenomenon was not seen in non-pregnant RLS patients (P =  0.65). Vitamin B12 (P =  0.59) and B1 (P =  0.362) deficiencies were not found in RLS patients. Oral vitamin B6 significantly improved primary RLS (P < 0.0001), while vitamin D did not (P =  0.05). Oral vitamin C (P < 0.00001), E (P < 0.0001), and vitamin C +  E (P < 0.00001) all significantly improved hemodialysis-associated RLS with equal efficacy. Vitamin C is equivalent to 0.18 mg of pramipexole for the treatment of RLS (P =  0.81). In this meta-analysis, low vitamin D levels were found in patients with RLS, low folate levels were associated with RLS only in pregnant women, and vitamin C/E/B6 may improved symptoms in patients with RLS. These results suggest that vitamin deficiency or insufficiency may be related to the pathogenesis of RLS.